Incidental parasitic infestations in surgically removed appendices: a retrospective analysis - Aydin Özgür (BMC, 2007)
Abstract Background Appendiceal parasites can cause symptoms of appendiceal pain, independent of microscopic evidence of acute inflammation. The diagnosis of a parasitic infestation is generally achieved only after the pathologic examination of the resected appendices. Patients/Methods Pathology department records were reviewed for all patients who required an operation for symptoms of acute appendicitis between 2000 and 2006. The specimens which were pathologically diagnosed to contain parasites were reevaluated for features of acute inflamation, and parasite type. The medical records were reviewed in detail to achieve a diagnostic score(Eskelinen). Radiologic imaging findings were correlated, if present. Results Of the 190 appendectomies performed, 6 specimens (3,15%) were found to contain parasites(4 Enterobius vermicularis, 2 Taenia subspecies). Appendectomies with Taenia showed acute inflamation, while acute inflamation was absent in the ones with Enterobius vermicularis. The Eskelinen score was higher than the treshold in two cases with an acute inflamation, and in two without. Ultrasound scans, and a computed tomography scan were performed in 5 patients. In 3 of 4 bland appendices, results favored acute appendicitis. Conclusion The diagnosis of gastrointestinal parasites is not only made by examining the stool but the diagnosis can be made by histology from surgical specimens. Timely diagnosis and appropriate therapy might prevent probable future complications that may necessitate surgical procedures, at least in some of the patients. The clinical management of these infections is different from that for classical appendicitis.